Patient-reported outcomes used actively in cancer patients undergoing antineoplastic treatment: A mini-review of the Danish landscape - Helle Pappot; Gry Assam Taarnhøj, MD; Line Bentsen; Rasmus Blechingberg Friis; Christina Bæksted; Mille Guldager Christiansen; Cecilie Holländer-Mieritz; Pia Krause Møller; Ida Marie Lind Rasmussen; Trine Lund-Jacobsen; Dag Rune Stormoen; Lærke K. Tolstrup (Computational and Structural Biotechnology Journal)
Introduction: Many studies using Patient-reported outcomes (PRO) data have been conducted to monitor symptoms and health-related quality of life during follow-up after cancer treatment. However new ways of using (e)PROs have emerged. We aimed to explore the Danish landscape of the use of PRO in a research setting, where PRO is used actively in cancer patients undergoing treatment, and give an overview of how it is embraced by patients and clinicians. Methods and materials: A literature search was performed in June 2023, using the keywords Denmark, cancer, and patient-reported outcomes. An expert on literature searches identified the search terms, and double screening was performed at both abstract and screening levels and full-text stage. The software tool Covidence was used. Results: 467 articles were retrieved and 19 studies were included. They described the type of ePRO instrument used and the application of active ePRO i.e. a dialogue tool in the clinical encounter, release of alerts to clinicians, and enhancement of self-management. Finally, a development in the use of active ePROs over time is elucidated and we show how it is embraced by patients and clinicians. Conclusion: This mini-review gives an overview of how ePRO solutions are tested in oncological research in Denmark and embraced by patients and clinicians. ePRO solutions in a Danish setting seem well-suited for self-management. However, if more impact is warranted, clinicians need to engage in reviewing and using ePROs. Moreover, for successful implementation, the integration of ePROs in electronic health records must be supported by IT specialists and management.